UNGKAPAN BUDAYA DALAM KARYA SASTRA REMAJA: ASPEK-ASPEK KARAKTER REMAJA AMERIKA DALAM PRADA AND PREJUDICE KARYA MANDY HUBBARD - Mirahayuni, Ni Ketut; Supsiadji, Mateus Rudi (Hasta Wiyata, 2019)
Culture-bound words has become potential issues in understanding texts due to their specific connotation and implication in the language expressing the culture. Since language is not merely a classification of a set of general and universal concepts, but more importantly that each language articulates or organizes the world differently, then concepts may be distinctly encapsulated in different languages. Culture involves aspects of intellects and arts in a society. Elements of culture in a society involves customs, beliefs, lifestyle, attitude, social organization and habits and arts in the given society.The topic of the study is cultural-bound expressions in literary works as a product of a culture. The study focuses on cultural-bound expressions in young adult literature (YAL). YAL is chosen as the object of study for its phenomenal growth and development since late 20th century and early 21st century.  The study chooses Mandy Hubbard’s Prada and Prejudice (2009) as the data source due to the wide range aspects of American culture being presented in the work. The study found that the cultural bound expressions are found in various environments, including family, school, peer group and society. The study also discusses the ideas of freedom and individual rights, responsibility, morality and pragmatism as the underlying notions of the expressed cultural concepts being expressed in the character of the work. The study is expected to contribute to better cultural understanding of American teenage culture as expressed in young adult literature.  young adult literature, American values, cultural bound expressions